2021
DOI: 10.4103/jehp.jehp_747_20
|View full text |Cite
|
Sign up to set email alerts
|

Application of health belief model to predict COVID-19-preventive behaviors among a sample of Iranian adult population

Abstract: BACKGROUND: The novel coronavirus (COVID-19) has infected nearly 9.5 million people in 216 countries, areas, or territories in the world. The fight against the COVID-19 has become a very serious international challenge. The aim of this study was to determine the predictors of COVID-19-preventive behaviors using the health belief model (HBM). MATERIALS AND METHODS: This cross-sectional study was conducted with the participation of 558 samples from the adult population of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 31 publications
4
15
0
2
Order By: Relevance
“…Self-efficacy and perceived benefits were the strongest predictors of protective behaviors, followed by risk perception and perceived barriers. Our findings are in line with those of two studies in Iran (12,13). Alsulaiman and Rentner proposed self-efficacy, perceived barriers, and perceived benefits as key determinants of Middle East respiratory syndrome (MERS) prevention (14).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Self-efficacy and perceived benefits were the strongest predictors of protective behaviors, followed by risk perception and perceived barriers. Our findings are in line with those of two studies in Iran (12,13). Alsulaiman and Rentner proposed self-efficacy, perceived barriers, and perceived benefits as key determinants of Middle East respiratory syndrome (MERS) prevention (14).…”
Section: Discussionsupporting
confidence: 91%
“…The most important perceived barrier in the present study was the high cost of using personal protective equipment, which was similar to some previous studies (12,13,22). Thus, the removal of environmental barriers to health behaviors, especially face masks, should be considered by local policymakers.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are consistent with some previous studies. Mirzaei et al identified that HBM explained 29.2% of the variance of preventive behaviors of COVID-19 [ 34 ]. In another study by Fathian-Dastgerdi, HBM constructs explained 42% of the variance of preventive behaviors [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“… Mirzaei et al. (2021) carried out a cross-sectional study among 558 adult samples in Iran to investigate the predictor of Covid-19 preventive behaviours with the aid of the Health Belief Model.…”
Section: Introductionmentioning
confidence: 99%